Syntaxonomical classification of wet woodlands with Picea abies in Slovakia - Kucera, P. (Український ботанічний журнал, 2019)
Wet woodlands with domination of Norway spruce are floristically and ecologically distinctive element of coniferous forest
vegetation. However, specialized studies on this vegetation are considerably rare. In this survey the syntaxonomical classification
of 145 relevés of Sphagnum-rich and other wet woodlands with Picea abies from Slovakia is proposed. Eight plant communities
in the rank of association were differentiated. A distinctive feature of the association Sphagno acutifolii-Piceetum Zukrigl 1973
is the co-occurrence of species typical for climax supramontane woodlands on silicate bedrock of the alliance Piceion excelsae
Pawłowski ex Pawłowski et al. 1928 and species characteristic for woodlands of the class Vaccinio uliginosi-Pinetea Passarge 1968.
Consequently, this association is classified within the order Piceetalia abietis Pawłowski ex Pawłowski et al. 1928 and alliance
Piceion excelsae Pawłowski ex Pawłowski et al. 1928. The rest of wet Picea woodland associations are azonal stable communities
(Dauergesellschaften) distributed mostly in the montane zone and they differ floristically as well. Therefore those associations
are separated in the floristically well distiguishable order Sphagno palustris-Piceetalia P. Kučera 2019 and they are subdivided into
three syntaxa in the rank of alliance: (1) alliance Sphagno palustris-Piceion P. Kučera 2019 comprising the communities limited to
nutrient-poor habitats with a shallow peat layer or hydromorphic soils with a substantial raw humus layer: Soldanello montanae-
Piceetum Volk in Br.-Bl. et al. 1939, Leucobryo glauci-Piceetum abietis Šomšák ex P. Kučera 2019, Sphagno palustris-Piceetum
Šomšák 1979, Equiseto sylvatici-Piceetum Šmarda 1950, and the Carex rostrata-Picea abies community; (2) alliance Stellario
nemorum-Abietion albae P. Kučera 2019 with the species-rich spring related association Stellario nemorum-Abietetum albae P.
Kučera 2019; (3) base rich alliance Valeriano dioicae-Abietion albae P. Kučera 2019 with the association Valeriano dioicae-Abietetum
P. Kučera 2019. Formal definitions and description of species composition of the units are given, as well as brief information on
their distribution in Slovakia. Several syntaxonomical and nomenclatural notes are provided in the supplement. Вологі ліси з домінуванням ялини звичайної (Picea abies) є флористично та екологічно відмінним елементом рослинності хвойних лісів. Однак спеціальні дослідження цієї рослинності є доволі рідкісними. У нашому дослідженні проведено синтаксономічну класифікацію 145 геоботанічних описів сфагнових та інших вологих лісових масивів із участю Picea abies зі Словаччини. Відмічені вісім рослинних угруповань у ранзі асоціації. Відмінною рисою асоціації Sphagno acutifolii-Piceetum Zukrigl 1973 є трапляння як видів, характерних для клімаксових супрамонтанних лісових масивів на силікатних породах з союзу Piceion excelsae Pawłowski ex Pawłowski et al. 1928, так і видів, характерних для лісових масивів із класу Vaccinio uliginosi-Pinetea Passarge 1968. Отже, ця асоціація належить до порядку Piceetalia abietis Pawłowski ex Pawłowski et al. 1928 та союзу Piceion excelsae Pawłowski ex Pawłowski et al. 1928. Решта асоціацій вологих лісів із участю ялини – це азональні стійкі угруповання (Dauergesellschaften), які поширені переважно в монтанній зоні і є флористично відмінними. Тому ці асоціації відокремлюються у флористично чітко відокремленому порядку Sphagno palustris-Piceetalia P. Kučera 2019 і поділяються на три синтаксони у ранзі союзу: (1) союзу Sphagno palustris- Piceion P. Kučera 2019, що включає угруповання, пов'язані з бідними на поживні речовини оселищами з поверхневим торфовим шаром або гідроморфними ґрунтами із значним шаром гумусу: Soldanello montanae-Piceetum Volk in Br.-Bl. et al. 1939, Leucobryo glauci-Piceetum abietis Šomšák ex P. Kučera 2019, Sphagno palustris-Piceetum Šomšák 1979, Equiseto sylvatici-Piceetum Šmarda 1950 та угруповання Carex rostrata-Picea abies; (2) союзу Stellario nemorum-Abietion albae P. Kučera 2019 з асоціацією Stellario nemorum-Abietetum albae P. Kučera 2019 з різноманітними весняними видами; (3) союзу Valeriano dioicae-Abietion albae P. Kučera 2019 на багатих основами ґрунтах з асоціацією Valeriano dioicae- Abietetum P. Kučera 2019. Подано формальні визначення та описи видового складу цих одиниць, а також стислу інформацію про їхнє поширення у Словаччині. Деякі синтаксономічні та номенклатурні примітки наведено в додатку.